Competition and quality of care under regulated fees: Evidence from Ghana - Adolf Kwadzo Dzampe; Shingo Takahashi (Health Economics Review, 2022)
Background: How competition afects the quality of care is still not well understood empirically because of limited and mixed results. This study examined whether competition leads to higher or lower quality health outcomes in Ghana. Methods: We used administrative claims data of hypertension patients for 2017 - 2019 (36 months), and an instrumental variable method to examine the effect of competition, measured as an increase in district doctorto-population ratio on hospital-level ambulatory care sensitive condition hospitalization and in-hospital death rates. Results: Overall, we found that an increase in doctor density improves the quality of care for hypertension patients in Ghana. That is, when there are more doctors, fewer patients are hospitalized, and the risk of in-hospital deaths decreases. This result is robust to analyses at the individual and district population levels for ambulatory care sensitive hospitalizations rate. Conclusions: Our fndings suggest that in the presence of physician-induced demand, competition can lead to improvement in the quality of care, possibly through improved access to healthcare and increased physician time and contact per patient. Future health policies need to consider possible welfare benefts of induced medical services and training more doctors.
Keywords: 330; Competition; Physician-induced demand; Doctor-to-population ratio; Quality of care; Hypertension; Ambulatory care sensitive hospitalization; Ghana